Design of catalytic and functional carbon nanoreactors - Aygun, Mehtap (2017)
The work presented in this thesis describes the development and applications of hollow carbon nanostructures both as the catalytically active, magnetically separable carbon nanoreactors, and electrodes for electrocatalytic reactions. The work is separated into three distinct parts, the formation of carbon nanoreactors of different diameters and shapes in which the effect of confinement imposed by the nanotube is probed in exploratory hydrogenation reactions, the functionalisation of carbon nanoreactors with magnetic nanoparticles for magnetically separable catalyst supports, and the development of new hybrid metal-carbon nanoreactors as efficient electrocatalysts for hydrogen fuel cell applications. In the first part of the thesis, a Ru3(CO)12 precursor was successfully inserted into carbon nanoreactors of different diameters – very narrow single walled carbon nanotubes (SWNTs, DSWNT ~1.5 nm) and much wider hollow graphitised carbon nanofibers (GNFs, internal dGNF ~50 nm) using sublimation followed by the formation of uncoated metallic Ru nanoparticles via thermal decomposition. The resultant RuNPs@SWNT and RuNPs@GNF nanoreactors were then tested in hydrogenation reactions using a high pressure scCO2 batch reactor, where the excellent diffusivity and mass transfer properties of scCO2 as solvent enabled the efficient delivery of the reagents to the catalyst surface within the narrow nanoreactors. RuNPs confined in the narrowest channels of SWNT was observed to be highly active and selective in competitive hydrogenation reaction of alkenes, but concurrently reduce the accessible volume of the SWNTs by 30-40 % resulting in lower overall turnover numbers (TONs). In contrast, RuNPs confined in wider GNFs were entirely accessible and indicated outstanding activity in comparison to unconfined RuNPs on the outer surface of SWNTs or carbon black. In the second part of the work, GNFs sidewalls were functionalised by non-covalent attachment of commercial graphene-like carbon coated magnetic Co nanomagnets (Co@Cn) exploiting van der Waals forces via dispersion in an organic solvent using ultrasonic treatment, and by the in situ formation of carbon coated iron nanomagnets (Fe@Cn). A number of experiments were carried out to find the minimum amount of nanomagnets required to enable complete separation of the nanotubes from the solution with an external magnetic field. Characterisation of this composite material by high resolution transmission electron microscopy (HRTEM) showed that Co@Cn and Fe@Cn successfully attached to the GNFs. Magnetic functionalisation steps were then combined with uncoated, palladium and platinum nanoparticle catalyst formation and the resultant catalytically active and magnetically separable hybrid materials were investigated in the reduction of nitrobenzene. The recyclability and stability of these magnetic and catalytic nanoreactors were studied in the reduction of nitrobenzene using magnetic recovery, and only negligible catalyst loss (< 0.5% by wt.) was observed over 5 cycles in comparison to that of filtration based catalyst recovery (>10% catalyst loss by wt.). In the third part, GNFs were shortened by ball milling and combined with palladium catalyst to form (PdNPs/-PdNPs@)s-GNF using a novel procedure and the resultant activity and stability towards hydrogen evolution and hydrogen oxidation reactions (HER/HOR) in acid media was studied. (PdNPs/-PdNPs@)s-GNF exhibited enhanced activity and excellent durability during 30000 electro-catalytic cycles in HER compared to that of state-art commercial Pt/C which exhibited decreasing activity and poor durability during the cycling in acid. Moreover, s-GNF demonstrated an enhanced HER activity and stability during 5000 cycles. HRTEM revealed some chemical transformations at the step edges within GNF during the electrochemical cycling contributing to durability of the electrocatalyst. Overall, the superior HER/HOR activity and durability was attributed to the corrugated morphology of s-GNF, and therefore the ability to stabilise the Pd nanoparticles at the graphitic step-edges effectively through strong bonding and synergetic effects between the Pd and s-GNF support. These results clearly indicate that carbon nanoreactors as catalyst supports and electrocatalystd show significant promise for a variety of chemical reactions.